Spatial variability models of CO2 emissions from soils colonized by grass (Deschampsia antarctica) and moss (Sanionia uncinata) in Admiralty Bay, King George Island - Mendonca, Eduardo de Sa; La Scala, Newton [UNESP]; Panosso, Alan Rodrigo [UNESP]; Simas, Felipe N. B.; Schaefer, Carlos E. G. R. (Cambridge University Press, 2011)
Soil CO2 emission is an important part of the terrestrial carbon cycling and is influenced by several factors, such as type and distribution of vegetation. In this work we evaluated the spatial variability of soil CO2 emission in terrestrial ecosystems of maritime Antarctica, under two contrasting vegetation covers: 1) grass areas of Deschampsia antarctica Desv., and 2) moss carpets of Sanionia uncinata (Hedw.) Loeske. Highest mean emission was obtained for the Deschampsia (4.13 mu mol m(-2) s(-1)) developed on organic-rich soil with a strong penguin influence. The overall results indicate that soil temperature is not directly related to the spatial pattern of soil CO2 emission at the sites studied. Emission adjusted models were Gaussian and exponential with ranges varying from 1.3 to 2.8 m, depending on the studied site and vegetation cover.
Keywords: Cryosols; Geostatistics; greenhouse gases; maritime Antarctic; soil carbon; Soil respiration